Online Product Review analysis for Sentiments - Arora, Ishan; Singh, Gagandeep; Kumar, Lokesh (International Journal of Computer Sciences and Engineering, 2025)
Buying and selling of things are a major part of human’s since early ages , but with the development of the online market the trade got shifted from usual market to online for ease of everyone .Internet (www) has been a resource to get the user’s review about the particular thing he had purchased. There are 2.4 billion active online users, who write and read online and use internet around us [1]. It will also help the companies to know what the problem the customers are facing in their use of the product. This will help the company to make better product and will surely help the customer to buy a product will large positive value [2]. With the help of the given system we classify the reviews. The paper will try to compare the various technique used to find out the opinion of the users .The proposed System will use the general algorithms of AI to find out the answer to this problem which are described in details in this paper.